Fallas en la gestión de la logística inversa del sector textil y confección en Bogotá, una descripción causal (2023)
The increase in the consumption of clothing year after year generates a growing demand for raw materials and, therefore, large amounts of waste from the textile and clothing process with an environmental impact on the air, land and water. The research specifies the amount of waste generated by 7 companies in Bogota D.C. during Q1 of the current year, after having learned about their production processes through direct observation, which allowed categorizing the textile waste by activity in Spinning (4. 106.4 kg), Washing and dyeing of fabrics (10,500 m3), Garment making (1,203 kg), Garment finishing (511 kg), Not specified (50 kg) and Others (2.76 kg), finding that Lycra (12% - 407 kg), Cotton (10% - 343.57 kg) in addition to Rayon (9.7% - 340 kg) are the material that was generated to a greater extent. These critical activities were listed in a Leopold matrix, which showed not only a negative environmental impact in each component by exceeding the reference of 100 units (Soil -306 units, Water -235 units and Air -245 units), values attributed not only to the high volume generated but also to the lack of management strategies for this remnant. It is important to identify the quantity and environmental risk of textile waste in order to prioritize action plans. Once the internal processes of the companies with their respective direct flows have been identified, the opportunity to apply material recovery activities for recycling, reuse or channeling is related, exemplifying successful cases. To conclude, an analysis of the reasons why companies do not recover value from this remnant is presented, among them the lack of knowledge of strategies that provide technical support from the government or private companies in terms of training, the failure to obtain an economic benefit that covers the effort of capturing the material and transforming it and, finally, the lack of control in the generation of waste.